Unusual Cause of Diffuse Pleural Thickening (Malignant Pleural Mesothelioma Mimic): Undifferentiated Epithelioid Malignant Neoplasm - Jamal Al-Aghbari; Amira Al Badi; Radiya Al Ajmi; Saif Al Mubaihsi (Oman Medical Journal)
The symptoms of malignant pleural mesothelioma can be mimicked by some other malignancies, clinically and radiologically. We describe a case of a 57-year-old man whose clinical and radiological findings were consistent with malignant pleural mesothelioma; however, a pleural biopsy showed undifferentiated epithelioid malignant neoplasm.